Strain Fluctuations Unlock Ferroelectricity in Wurtzites - Steven M. Baksa; Simon Gelin; Seda Oturak; R. Jackson Spurling; Alireza Sepehrinezhad; Leonard Jacques; Susan E. Trolier‐McKinstry; Adri C. T. van Duin; Jon‐Paul Maria; Andrew M. Rappe; Ismaila Dabo (Advanced Electronic Materials)
Abstract Ferroelectrics are of practical interest for non‐volatile data storage due to their reorientable, crystallographically defined polarization. Yet efforts to integrate conventional ferroelectrics into ultrathin memories have been frustrated by film‐thickness limitations, which impede polarization reversal under low applied voltage. Wurtzite materials, including magnesium‐substituted zinc oxide (Zn,Mg)O, have been shown to exhibit scalable ferroelectricity as thin films. In this work, the origins of ferroelectricity in (Zn,Mg)O are explained, showing that large strain fluctuations emerge locally in (Zn,Mg)O and can reduce local barriers to ferroelectric switching by more than 40%. Concurrent experimental and computational evidence of these effects are provided by demonstrating polarization switching in ZnO/(Zn,Mg)O/ZnO heterostructures featuring built‐in interfacial strain gradients. These results open up an avenue to develop scalable ferroelectrics by controlling strain fluctuations atomistically.